Ball Milled Si-W Alloys: Part I. Microstructural and Phase Evolution during Ball Milling. Issue 6 (8th April 2019) - Liu, Yijia; Scott, Benjamin; Obrovac, M. N.
Abstract : In this first part of a two-part study of the synthesis, microstructure and electrochemical properties of ball milled silicon-tungsten alloys (Si100-x Wx, x = 15, 20, 25, 30), the ball milling process is discussed in detail. The phase evolution was quantitatively followed during milling, allowing for a detailed understanding of the ball milling process. A volume element model of the process was developed that uses only three parameters that are directly related to the milling conditions. This model was found to well explain the ball milling process and suggests that energy initially accumulates in the Si and W powders after every ball collision. Eventually the stored energy overcomes activation energy for the reaction of Si and W to form Si2 W. The kinetics of these processes and the tendency for reactants to cake in the mill are important parameters to consider for the practical synthesis of different Si-metal alloy materials.